Gangguan Kesehatan Akibat Pencemaran Merkuri (Hg) pada Penambangan Emas Ilegal - Masruddin Masruddin; Surahma Asti Mulasari (Poltekkes Kemenkes Maluku, 2021)
Gold mining activities can increase people's income and be detrimental if the correct processing process does not follow the implementation. This illegal gold mining and processing of gold ore use mercury. In the gold laundering process, who should carry out mercury with the correct procedures and knowledge. Still, in this illegal gold mining, the miners wash gold using mercury without using personal protective equipment so that the miners are in direct contact with the mercury used. Continuous, direct contact with heavy metals can cause an increase in chemical elements in the body caused by the bioaccumulation system. The purpose of this literature review is to determine the health problems caused by heavy metals in illegal gold mining. The database searches used are Garuda Portal and Google Scholar. There were 24 articles, and only ten were used, which were suitable through analysis of objectives, suitability of topics, analysis of results, and research locations. Based on the results of studies conducted, miners suffer from chronic and acute diseases. Chronic diseases suffered are liver dysfunction, decreased leukocytes, paralysis of limbs, numbness, and tremors. Symptoms felt by Parkinson's disease are constantly shaking hands and feet, facial muscles always moving involuntarily. Lips move unconsciously, lack passion for activities, difficulty sleeping, sometimes peaking emotions, poor memory, cramps during cold weather conditions, and often feel anxious. In contrast, the acute diseases that arise are acute poisoning, diarrhea, ARI, eye disease, vertigo, miscarriage, skin disease.